Integrative analysis of blood transcriptome profiles in small-cell lung cancer patients for identification of novel chemotherapy resistance-related biomarkers - Yang, Fang; Fan, Jinhua; Yang, Runxiang; Cun, Yupeng (Frontiers in Immunology, 2024)
Chemoresistance constitutes a prevalent factor that significantly impacts the survival of patients undergoing treatment for small-cell lung cancer (SCLC). Chemotherapy resistance in SCLC patients is generally classified as primary or acquired resistance, each governed by distinct mechanisms that remain inadequately researched. In this study, we performed transcriptome screening of peripheral blood plasma obtained from 17 patients before and after receiving combined etoposide and platinum treatment. We first estimated pseudo-single-cell analysis using xCell and ESTIMATE and identified differentially expressed genes (DEGs), then performed network analysis to discover key hub genes involved in chemotherapy resistance. Results showed a significant increase in class-switched memory B cell scores across both chemotherapy resistance patterns, indicating their potential crucial role in mediating resistance. Moreover, network analysis identified PRICKLE3, TNFSF10, ACSL1 and EP300 as potential contributors to primary resistance, with SNW1, SENP2 and SMNDC1 emerging as significant factors in acquired resistance, providinge valuable insights into chemotherapy resistance in SCLC.